2019
DOI: 10.1108/arj-05-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Quality and quantity of FTSE-100 segmental information reporting

Abstract: Purpose This study aims to explore the impact of international financial reporting standard no. 8 (IFRS 8) on segmental information reporting (SIR) after the post-implementation review (PIR) issued by international accounting standards board (IASB). This impact is examined in relation to quality and quantity as SIR dimensions represent, respectively, the level of reported items and segments. As a complement to this, the chief operating decision maker (CODM) identity is considered to understand the patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The overall insight achieved through the use of Models (1) and (2) advances our understanding about how ERP enables the quality (M‐V) dimension of SIR. This supports earlier research, which reported an increasing trend in relation to both M‐SIR and V‐SIR in FTSE‐100 companies (Mardini and Ammar, 2019). This may be due to the best practices of cost allocation (Hyvönen, 2003) and budgeting (Jackling and Spraakman, 2006) that are offered by ERP.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The overall insight achieved through the use of Models (1) and (2) advances our understanding about how ERP enables the quality (M‐V) dimension of SIR. This supports earlier research, which reported an increasing trend in relation to both M‐SIR and V‐SIR in FTSE‐100 companies (Mardini and Ammar, 2019). This may be due to the best practices of cost allocation (Hyvönen, 2003) and budgeting (Jackling and Spraakman, 2006) that are offered by ERP.…”
Section: Resultssupporting
confidence: 92%
“…This insight explains the link between internal (management accounting) and external (financial accounting) parties through SIR’s quantity dimensions (Cohen and Karatzimas, 2013). Specifically, it explains why the trend in relation to reported segments published by FTSE‐100 companies has generally increased in NoS (Mardini and Ammar, 2019). This may be ascribed to the value creation achieved through ERP’s characteristics, and this may explain: (i) the motivations of FTSE‐100 companies in pursuing ERP (Ugrin, 2009), and (ii) an increasing trend in the number of reported segments globally (Kang and Gray, 2013; Aleksanyan and Danbolt, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Further, they concluded that the adoption of IFRS-8 in a variety of different countries led to an increase in the number of reported segments. Moreover, the number of items provided per segment tended to increase under IFRS-8, especially post the implementation of the 2012 review (Mardini and Ammar 2019). On the other hand, some previous research (e.g., Mardini, Tahat, and Power 2018;Birt, Joshi, and Kend 2017;Kajüter and Nienhaus 2017) has investigated the value relevance of SR under IFRS-8.…”
Section: Sr and Corporate Performancementioning
confidence: 90%
“…These previous review studies drew attention to inconsistency and a knowledge gap in understanding the separate impacts of ERP and SR, on CP. It has recently been found that the content of both mandatory and voluntary SR were raised following IFRS operationalisation (Mardini and Ammar 2019). However, understanding the extent to which this operationalisation may influence CP is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation